Nurses' perceptions of the impact of the aged care reform on services for residents in multi‐purpose services and residential aged care facilities in rural Australia. (23rd June 2016) - Henderson, Julie; Willis, Eileen; Xiao, Lily; Toffoli, Luisa; Verrall, Claire
Abstract : Aim: To understand nurses' perceptions of the impact of the aged care reform on care and services for residents in multi‐purpose services (MPS) and residential aged care facilities (RACF) in rural South Australia. Methods: An interpretative study using semi‐structured interviews. Participants comprised registered and enrolled nurses working with aged care residents in rural South Australia. Eleven nurses were interviewed, of these seven worked in MPS and four in RACF. Results: Data were analysed for similarities and differences in participants' experiences of care delivery between MPS and RACF. Common issues were identified relating to funding and resource shortfalls, staffing levels, skill mix and knowledge deficits. Funding and staffing shortfalls in MPS were related by participants to the lower priority given to aged care in allocating resources within MPS. Nurses in these services identified limited specialist knowledge of aged care and care deficits around basic nursing care. Nurses in RACF identified funding and staffing shortfalls arising from empty beds due to the introduction of the accommodation payment. Dependence upon care workers was associated with care deficits in complex care such as pain management, medication review and wound care. Conclusion: Further research is needed into the impact of recent reforms on the capacity to deliver quality aged care in rural regions.